Strengthening Legal Frameworks To Address Nominee Agreements In Land Ownership: Policy Recommendations For Indonesia - Haspada, Deny (Indonesian Journal of Humanities and Social Sciences, 2023)
This research examines the legal frameworks addressing nominee agreements in land ownership between foreign nationals and Indonesian citizens, with a focus on developing policy recommendations to strengthen these frameworks. Nominee agreements are often utilized to circumvent restrictions on land ownership by foreign nationals, posing significant legal and regulatory challenges. This study employs a qualitative approach, combining doctrinal analysis and empirical research, to evaluate the current legal provisions and their enforcement. A comparative analysis with international practices is conducted to identify best practices and potential improvements for Indonesia. Key findings highlight significant gaps and weaknesses in the existing legal framework, which undermine the effectiveness of land ownership regulations and pose risks to national sovereignty and economic stability. The study proposes comprehensive policy recommendations aimed at enhancing transparency, accountability, and enforcement mechanisms in land ownership regulations. These recommendations are designed to foster a more robust and cohesive legal framework that can effectively address the complexities of nominee agreements and safeguard Indonesia's land resources.